An Overview of Naturally Synthesized Metallic Nanoparticles - Mariappan Vignesh, Puthamohan Vinayaga Moorthi (Journal of Applied Pharmaceutical Science, 2017)
Nanotechnology is a powerful technology offers wide spectrum of devices, drugs etc for the welfare of human and other living organisms. Nanoparticles are the tiny molecule in the size of 1-100nm acting as potential antimicrobial, anticancer, Anti-Larvicidal and Antiparasitic Agents. Among the nanoparticles deployed, silver and gold nanoparticles have been greatly used against multidrug resistant microbes like Staphylococcus aureus, vector mosquitoes like Aedes aegypti, Anopheles stephensi and Culex quinquifasciatus as well as wide range of cancer Cell lines like MCF-7, Hep G2, etc. In the recent years, identification of dynamic nanoparticles, possessing antimicrobial, anti-larvicidal and anticancer activity, becomes important for defending the existing multitude of diseases spreading to human beings. In this context, this review was prepared to measure the dynamics of bioactive nanoparticles extremely used against pathogens, cell lines and vectors.
Keywords: Nanoparticles, Antimicrobial, Anticancer, Larvicidal activity, MCF-7.